2006
DOI: 10.1262/jrd.18069
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Ovarian Granulosa Cell Death by Pro- and Anti-apoptotic Molecules

Abstract: Abstract. In the mammalian ovary, follicular development and atresia are closely regulated by cell death and survival-promoting factors, including hormones (gonadotropins) and intraovarian regulators (gonadal steroids, cytokines, and intracellular proteins). Several hundred thousand primordial follicles are present in the mammalian ovary; however, only a limited number of primordial follicles develop to the preovulatory stage and ovulate. The others, more than 99% of follicles, will be eliminated via a degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
132
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 104 publications
(101 reference statements)
4
132
0
2
Order By: Relevance
“…34 Previous studies have demonstrated that both pathways are involved in GCs apoptosis. 26,35 However, as shown in the present study, we found that GC apoptosis driven by EGR1 overexpression induced hallmarks of mitochondrial apoptosis (BCL2, CAS-PASE-9 and CASPASE-3). In contrast, EGR1 overexpression had no effect on the components of the death receptor pathway (CASPASE-8).…”
Section: Up-regulation Of Egr1 Induces P53 But Not Pten Activationsupporting
confidence: 58%
“…34 Previous studies have demonstrated that both pathways are involved in GCs apoptosis. 26,35 However, as shown in the present study, we found that GC apoptosis driven by EGR1 overexpression induced hallmarks of mitochondrial apoptosis (BCL2, CAS-PASE-9 and CASPASE-3). In contrast, EGR1 overexpression had no effect on the components of the death receptor pathway (CASPASE-8).…”
Section: Up-regulation Of Egr1 Induces P53 But Not Pten Activationsupporting
confidence: 58%
“…Overexpression of pFADD and pprocaspase-8 induced cell death in the HeLa-K cells. To date, we have investigated the follicular atretic mechanisms of follicular atresia in porcine ovaries [18][19][20][21][22][26][27][28][29][30][31] and have shown that g r a n u l o s a c e l l a p o p t o s i s i s a d o m i n a n t phenomenon in follicular atresia. Therefore, we examined whether overexpressed pFADD and pprocaspase-8 can induce apoptosis in the granulosa cells of human, murine, and porcine origin (KGN, KK1 and JC410, respectively).…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
“…We previously reported that death ligand/ receptor systems act as initiators of apoptosis in porcine granulosa cells [22,30,31] and showed that an intracellular inhibitory protein, cFLIP, inhibits apoptosis in granulosa cells by binding with the D E D o f F A D D a n d / o r p r o c a s p a s e -8 a n d interrupting the recruitment of procaspase-8 to FADD [29,30]. In the present study, we showed that both the molecular construction and function of apoptotic signaling factors are highly conserved.…”
Section: Apoptosis Inductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…58: [112][113][114][115][116] 2012) I n mammalian ovaries, more than 99% of follicles degenerate at various stages of follicular growth and development [1]. The degeneration is explained, at least in part, by the apoptosis of granulosa cells [2][3][4][5][6]. In porcine ovarian follicles in the early stages of atresia, characteristics typical of apoptosis are observed in scattered granulosa cells, but not in cumulus cells, oocytes or the cells of internal or external thecal layers [7].…”
mentioning
confidence: 99%